PHYSICS OF CAPILLARITY AND COFFEE BREWING PROCESS - Замкова, С.; Сосновська, А.; Матвеева, Татьяна; Коваль, А.; Стецюра, Д. (Modern engineering and innovative technologies, 2024)
The article considers the physical phenomenon of capillarity and its application in the process of brewing coffee. It discloses factors affecting the extraction efficiency and taste of the beverage, such as surface tension, adhesion, coffee particle size,